Gestational Weight Gain and Its Relation to Maternal, Fetal and Neonatal Sequelae: A Future Dilemma - Gul, Hina; Hussain , Shahazadi Saima; Munir, Aiman; Bawar, Shandana (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study aimed to determine the frequency of women with gestational weight gain (GWG) from recommended values in pregnancy and to establish the association of GWG with the mode of delivery (vaginal delivery (VD), instrumental delivery(ID), cesarean section(CS) and neonatal outcomes( low birth weight (LBW), low APGAR score, macrosomia, stillbirth (SB) and neonatal intensive care unit admissions(NICU). METHODOLOGY The prospective study was done in the Department of Obstetrics & Gynaecology LRH Peshawar. A total of 140 women were included in this study by non-probability consecutive sampling technique. Those with congenital anomalies having known medical disorders were excluded. Ethical approval and Informed consent were obtained before the examination. Data were collected and analysed on SPSS version 22. RESULTS The mean age was 29.4 ± 5.1 years. The mean first trimester BMI of the study sample was 25.2 ± 3.4kg/m2, while the mean BMI in 3rd trimester was 27.7± 2.3 kg/m2. GWG was recorded in 52 (37.1%) women. The mean GWG was calculated to be 12.9 kg ± 2.5. Mode of delivery was VD in 60(42.9%) women, ID in 50 (35.7%), and CS was done in 30(21.4%0) women. LBW in 15(10.7%), low APGAR score was recorded in 32(22.9%), macrosomia in 14(10%), SB in 12 (8.6%) and NICU admission in 39(27.9%). CONCLUSION GWG is common in pregnant women; however, there was no statistically significant association between GWG and mode of delivery or neonatal outcomes.